Effects of blood flow patent and cross-sectional area on hemodynamic into patient-specific cerebral aneurysm via fluid-structure interaction method : A review - Nurul Najihah, Mohd Nazri; Muhammad Uzair, Matalif; Mohd Azrul Hisham, Mohd Adib (IOP Publishing Ltd., 2020)
Fluid-structure interaction (FSI) simulation is carried out to investigate the blood flow analysis in different patient-specific cerebral aneurysms. In this study, we reviewed the studies done on the numerical simulation of blood flow in patient-specific aneurysm by using FSI analysis methods. Based on these studies, the wall shear stress (WSS) plays an important role in the development, growth, and rupture of the cerebral aneurysm. Prediction of the hemodynamic forces near the aneurysmal site helps to understand the formation and rupture of the aneurysms better. Then most of the aneurysms studied are located in the middle cerebral artery (MCA). In the existing considered, many researchers are more familiar with the experimental method in studies of blood flow through cerebral aneurysm compared to the numerical method. Nevertheless, numerical simulation of patient-specific cerebral aneurysms can give a better understanding and clear visualization of WSS distribution and fluid flow pattern in the aneurysm region.